Role of Serum Bilirubin as a Predictive Biomarker for Appendiceal Perforation in Patients Undergoing Emergency Appendectomy - Hafiz Muhammad Abdullah; Muhammad Zain Ul Abadin; VARDA ABID; HUSSAIN, ALTAF; MUHAMMAD ADNAN AKHTAR; MUGHIS AHMAD (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Appendiceal perforation is a severe perineal complication of acute appendicitis and is characterized by heightened morbidity, extended stay, and extended postoperative complication. Early diagnosis is still a clinical problem especially when it comes to emergencies. Serum bilirubin has become one of the potential biomarkers that predict complicated appendicitis. Objective: To assess whether serum bilirubin is an analysis biomarker of appendiceal perforation in patients who are exposed to emergency appendectomy. Methods: A prospective study of 100 patients with probable acute appendicitis who were subjected to emergency appendectomy was used. Preoperative clinical assessment, laboratory, such as serum total bilirubin, direct bilirubin, and indirect bilirubin, and imaging were carried out. Findings during the intraoperative phase were used to categorize cases as perforated and non-perforated. The bilirubin levels in the groups were statistically compared and then the ROC curve analysis to find the accuracy diagnosis and the best cut-off value was carried out. Results: 32 percent of the 100 patients had perforated appendicitis. The perforated group had a high mean total bilirubin level (2.21 + -0.58 mg/dL) as compared to non-perforated (1.08 + -0.32 mg/dL, p < 0.001). The level of direct and indirect bilirubin was also very high in perforated cases. An AUC of ROC analysis was 0.87 and an optimum bilirubin cut-off was 1.6 mg/dL (sensitivity 81, specificity 78). There was a comparatively high risk of postoperative complications like wound infection and length of stay in the perforated group. Conclusion: High serum bilirubin, especially above 1.6 mg/dL is an excellent predictive biomarker of appendiceal perforation. As it is simple, low cost, and is wide available, bilirubin measurement ought to validate part of routine examination in cases of suspected acute appendicitis in order to become efficient in diagnosing early and initiating surgery. More multicentric research is advisable to confirm cut-off levels and enhance its clinical usefulness.